MINORITY CULTURAL ADAPTATION AT DAARUT TAUHIID BOARDING SCHOOL FOR FEMALE STUDENTS - Handani, Tri; Budiman, Nandang; Syahri, Lia Mita (TERAPUTIK: Jurnal Bimbingan dan Konseling, 2024)
This article aims to analyze the level o cultural adaptation owned by female students with minority cultures who are in Sundanese majority culture area. This study uses quantitative descriptive research methods. The research sample consists of 35 active students of SMA Daarut Tauhiid Boarding School Putri who have cultures other than Sundanese culture. The instruments used was the Cross Cultural Adaptation Inventory (CCAI) questionnaire. Aspects of the instruments are about: 1) Emotional Resilience, 2) Flexibility/Openness, 3) Perceptual Acuity, and 4) Personal Autonomy. Data analysis using descriptive analysis. Based on the reliability test of the instrument, it was found that the Cronbach's alpha value was 0.73, which falls into the good category. Furthermore, based on the data analysis in the study, it was found that cultural adaptation among minority female students at Daarut Tauhiid High School was in the high category, with a percentage of 62.86%